Influence of Compaction, Gradations, and Stress Levels on Fatigue Performance of SMA-13 Mixtures - Jinshun Xue; Yingjun Jiang (Advances in Materials Science and Engineering)
The fatigue characteristics of the stone-mastic asphalt (SMA) mixture and pavement structure are the basis of SMA mixture pavement design. However, the fatigue performance of the SMA mixture compacted by a vertical vibration compaction method (VTM) has been rarely studied. This paper presents the indirect tensile fatigue test results of a laboratory investigation focused on the influence of compaction methods (Marshall compaction method, vertical vibration compaction method, and Superpave gyration compaction method), gradations (specification gradation and skeleton dense gradation), and stress levels on the fatigue performance of the SMA mixture with the nominal maximum particle size of 13.2 mm (SMA-13 mixture). Results showed that the fatigue life of the SMA-13 mixtures decreases linearly with the increase of the stress level under the same failure probability. The fatigue life of the SMA-13 mixture was 156% and 310% higher than that of the SGC and Marshall methods under the same loading stress, respectively. Furthermore, the fatigue life of the SMA-13 mixture with skeleton dense gradation was 55% higher than that of specification gradation. Through comparing the fatigue life of SMA-13 mixtures prepared under different compaction methods and gradations, the compaction methods of VTM and the skeleton dense gradation were recommended for SMA-13 mixture design.